THE USE OF R.A.P. PARAPHRASING STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION AT CLASS X.A3 IN SMKN 2 SINGARAJA IN ACADEMIC YEAR 2013/2014 - SUWANA, I.G.G.; ARTINI, L.P.; PISCAYANTI, K.S. (Universitas Pendidikan Ganesha, 2018)
The study was categorized as classroom action research which was done for the purpose of improving the students’ reading comprehension at Class X.A3 in SMKN 2 Singaraja in academic year 2013/2014 through the implementation of R.A.P Paraphrasing strategy. The study was done in two cycles where each cycle consisted of four main activities; planning, action, observation and reflection. To collect the data, there were three kinds of instrument used namely researcher’s diary, questionnaire, and tests. Furthermore, the data obtained in this study were analyzed quantitatively and qualitatively. The data gained in pre-test and post-tests were analyzed quantitatively, while the data from researcher’s diary and questionnaire were analyzed qualitatively. Based on the results of this study, it was found that the students’ reading comprehension at Class X.A3 in SMKN 2 Singaraja had improved significantly. It was indicated by the result of students’ tests on which in pre-test, from 35 students in total, there were only 14.29% students passing the school passing grade. But in post-test I, the number increased into 71.43% students, and finally in post-test II, the criteria of success had been reached as 85.71% students could successfully pass the standard passing score. In addition, the success of the study was also based on the results of the questionnaire as well as the researcher’s diary which showed the students’ positive attitudes toward the implementation of the R.A.P. Paraphrasing strategy in their reading activities. Keywords : reading comprehension, R.A.P. paraphrasing strategy, English subject in vocational school